Mappa Totius Mundi Adornata juxta Observationes Dnn Acadmiae Regalis Scientarum et nonnullorum aliorum, secundum annotations recentissimas - Lotter, Tobias Conrad, 1717-1777 L'Isle, Guillaume de, 1675-1726 (1765)
18th century Copper engraving handcolored with watercolor. Full color. Mounted on cloth. Relief shown pictorially. Printed in cartouche in middle of top border: "Mappa Totius Mundi Adornata juxta Observationes Dnn Acadmiae Regalis Scientarum et nonnullorum aliorum, secundum annotations recentissimas. Per G. de l'Isle Geographum Parisiis. Prostat nunc in Officina Tobiae Conradi Lotter Goegr. Et Chalcogr. Aug. Vind." Printed in cartouche in middle of bottom edge: "Annotatio. Autor redditit rationes in sur nova Introductione in Geographiam de mutationaly, quas fecit hac Mappa, sicut etiam de caeteris, quas in lucem edidit." Printed in the northern Pacific Ocean off the coast of North America: "Costa detecta a Don Ioan de Gama navigante ex China in Novam Hispanum." Written in pencil in upper right corner: "1715." Two hemisphere projections with insets of North and South Pole in upper left and upper right corners, respectively. Shows California as a peninsula. Of note, displays exploration route of many explorers and the year they explored including: Equitis de Charmont, Pelsarta (1629), Albelis Tasmani (1642), Mendanae et Quiri (1595), Magellan (1520), and Guetani (1542). The Arctic region is marked as "Terra Arcticae" and the whole northwest portion of North America is blank. Surrounding the title cartouche are four figures representing the four continents. Scale c.a. 1:70,000,0000. Tobias Conrad Lotter (1717-1777) was a German cartographer, engraver and publisher. He was one of the "better-known cartographers in the eighteenth-century German school" (Moreland and Bannister, 88). He worked as an apprentice to Funk. He married a daughter of Seutter in 1740. He then succeeded Seutter in 1756 and worked as partner to Albrecht, Seutter's son, and G. B. Probst, Seutter's son-in-law. Among his works are "Terra Sancta" (1759), "Sardinia and Corsica" (1764), "Russia, Turkey etc." (1769), "World" (1775-78, 1782), "New England and sh." (1779), "Pacific Ocean" (1781), "Russia" (1788), "Atlas Minor" (n.d.) and "Atlas Geographr. Portatilis" (Tooley, 401). Guillaume de L'Isle (1675-1726) was a major cartographer of the eighteenth century. He was the Prmier Geographe du Roi (1718) and studied mathematics and astronomy under Jacques Cassini. He took a "critical approach to the maps of his predecessors" (Moreland and Bannister, 131-2). Among his works are "globe, map of the world and the four continents" (1700), "Atlas de Geographie" (1700-12), "Mississippi" (1701) and posthumously, "Atlas Noveau" (1730-). His widow took over his business after his death and partnered with Philippe Buache (Tooley, 395). This map was most likely created in the early 1700s by de L'isle and revised and reprinted by Lotter. Source(s): Moreland, Carl and David Bannister. "Antique Maps: A Collector's Handbook." New York: Longman Group, Ltd., 1983. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979.